Senegal : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This Selected Issues paper analyzes Senegal's real effective exchange rate (REER) and external competitiveness. A REER significantly above its equilibrium, as determined by economic fundamentals, can impede a country's external competitiveness, calling for corrective macroeconomic measures. This paper finds no conclusive evidence of a REER overvaluation, implying that structural reforms are key to improving Senegal's external competitiveness. The paper also describes Senegal's export performance, developments of the REER, and an empirical analysis of the equilibrium REER. Structural measures of competitiveness are also illustrated.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet